1978
DOI: 10.1126/science.622555
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Myxedematosus Serum Stimulates Human Skin Fibroblast Proliferation

Abstract: Serum from patients with lichen myxedematosus, when added to exponentially growing normal human skin fibroblasts, stimulates DNA synthesis and cell proliferation. The degree of response in vitro is correlated with the extent of the disease in vivo and is specific for fibroblasts. The results suggest that there is a systemic factor (or factors) which may play a role in the etiology of diseases affecting the connective tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
7

Year Published

1979
1979
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(71 citation statements)
references
References 8 publications
1
63
0
7
Order By: Relevance
“…A benign monoclonal gammopathy is usually present and the patients show discrete lichenoid papules, which can be confluent or generalized [29]. Serum from these patients can stimulate proliferation in cultured fibroblasts [30]. Fibroblasts from the lesions produce more glycosaminoglycans and the ratio of HYA to sulphated glycosaminoglycans is increased [31].…”
Section: Lichen Myxoedematosusmentioning
confidence: 99%
“…A benign monoclonal gammopathy is usually present and the patients show discrete lichenoid papules, which can be confluent or generalized [29]. Serum from these patients can stimulate proliferation in cultured fibroblasts [30]. Fibroblasts from the lesions produce more glycosaminoglycans and the ratio of HYA to sulphated glycosaminoglycans is increased [31].…”
Section: Lichen Myxoedematosusmentioning
confidence: 99%
“…A serum factor which is distinct from the abnormal globulin and which stimulates proliferation of fibroblasts in tissue culture has been demonstrated. 8 Reticular erythematous mucinosis may represent still another variant of lichen myxedematosus, but it is not associated with any serum protein abnormality. l 6 The lesions occur on the chest and back, and appear as irregular, reticulated, erythematous macules and occasional papules.…”
Section: Review Of the Mucinoses Of Humans And Animalsmentioning
confidence: 99%
“…16 It was shown that serum of scleromyxedema patients with a monoclonal gammopathy stimulated the production of hyaluronic acid and prostaglandin E in fibroblast cultures but that isolated serum IgG failed to do so. 11,19 This suggests a pathogenetic role of other, yet-unknown circulating factors, such as interleukin 1, tumor necrosis factors, and transforming growth factor b, which are known to stimulate glycosaminoglycan synthesis. 16 Clinical remission of scleromyxedema after transplantation of autologous stem cells points to the bone marrow as a source of these circulating factors.…”
mentioning
confidence: 99%